Language change and linguistic diversity : studies in honour of Lyle Campbell - Costa Chacon, Thiago; Lee, Nala H.; Silva, W. D. L. (Edinburgh : Edinburgh University Press, 2022)
Explores advances in the fields of language documentation, language change and historical linguistics.
Includes bibliographical reference and indexes.
Print version record.
Added to collection customer.56279.3
Keywords: Campbell, Lyle; Linguistic change; Language and languages -- Variation; FOREIGN LANGUAGE STUDY -- General; Electronic books; Festschriften